Performance analysis and dimensional optimization of a 2URR-URU parallel mechanism with remote center of motion - CHE Linxian; LI Jie; WEN Shikun; JIANG Haiyi (Jixie chuandong)
ObjectiveWhen robots are used in the minimally invasive surgical fields such as puncture, biopsy, and ophthalmology operations, the end effector to pass through the fixed wound center and to perform rotations around it are required. For this purpose, a kind of parallel mechanism with the remote center of motion was designed.MethodsUsing the principle of the intersection of two planes, a novel 2URR-URU parallel mechanism with two rotational and one translational degrees of freedom was proposed to realize the remote center of motion for the minimally invasive surgery. The screw theory was applied to analyze its degree of freedom and to identify the motion characteristic. The position analysis model was established to obtain the analytical expressions of inverse displacement solutions to this mechanism. The velocity of the mechanism was analyzed by means of the screw algebra method, and the input and output Jacobian matrices were derived. On this basis, the possible singular configurations of the mechanism were investigated. The input and output transmission indices were used to evaluate the motion and force transmission performances of the mechanism. Furthermore, the evaluation indices for global transmission performances in the expected workspace of minimally invasive surgery were introduced. The expected workspace designed as the deviation type can enhance the global transmission performances of the mechanism. A constrained optimization model was constructed to formulate the design problem of dimensional parameters on the optimizing global transmission performance, and the hybrid social cognitive optimization algorithm was employed to solve this problem. A case of the dimensional optimization design of the mechanism was given.ResultsThe results show that the mechanism can meet the design requirements of the remote center of motion, and the presented model and algorithm for mechanism optimization are feasible and effective. At the same time, the global performance indices of the mechanism obtained by the optimization design are better than those of the experience design.